Choroid and Retinal Nerve Fiber Layer Thickness in Patients with Chronic Obstructive Pulmonary Disease Exacerbation - Özkan Kocamış; Duygu Zorlu (Journal of Ophthalmology)
Purpose. We aimed at measuring the choroid and retinal nerve fiber layer thickness with optic coherence tomography (OCT) in patients diagnosed with chronic obstructive pulmonary disease (COPD). Methods. A total of 60 patients with COPD and 23 healthy controls were evaluated in the scope of this prospective, observational study. COPD patients were divided into two groups as those that were stable and those with an exacerbation based on the Global Initiative for Chronic Obstructive Lung Disease (GOLD) classification. Subfoveal choroid thickness (SFCT) of the patients and the control group was compared by measuring the choroid thickness at points 1000 µm nasal and temporal to the fovea and the mean retinal nerve fiber layer (RNFL) thickness. Results. The subfoveal choroid thickness of the COPD patients in both the exacerbation and stable groups was found to be statistically significantly thinner than the control group (p=0.047 and p=0.046, resp.). No statistically significant difference was found between the subfoveal choroid thickness of the patients that were stable and those that had an exacerbation (p=0.813). No statistically significant difference was found between the mean RNFL, 1000 µm nasal, or 1000 µm temporal choroid thicknesses of the COPD patients and the control group (p=0.263, p=0.455, and p=0.611, resp.). Conclusion. Decreased subfoveal choroid thickness was found in the COPD patients both during an exacerbation and in the stable period, when compared to the control group. The mean RNFL thickness was similar in the exacerbation and stable period of the stable COPD patients when compared to the control group. This suggests that ocular findings might be important in terms of COPD morbidity. This trial is registered with www.chictr.org.cn/enIndex.aspx.